Proceso de atención de enfermería en paciente con pielonefritis - Ortega Riofrio, Sabrina Tatiana (Machala : Universidad Técnica de Machala, 2018)
Pyelonephritis is a high urinary tract infection characterized by bacterial invasion of the pelvis and renal parenchyma of one or both kidneys and may cause complications that compromise the patient's life. In the year 2016 nationwide were reported 1948 cases of Pyelonephritis of which 311 affected men and 1635 women because they are the most likely to contract this disease and others related to the urinary tract by their urogenital anatomy. Escherichia coli is the main bacterium responsible for most cases of pyelonephritis. The objective of this work was to elaborate the process of nursing care based on critical thinking in the evaluation, diagnosis, planning, execution and evaluation for the decision making in the patient's attention and in turn to relate it with the theory of Marjory Gordon, which makes it possible to evaluate the functional patterns that constitute a fundamental pillar in the identification of the real or potential problems in the individuals. We used a methodology based on the bibliographical research of sources such as the Internet, books, journal articles that were the fundamental basis for obtaining the necessary information in the elaboration of this research work. In conclusion, the action plans developed and applied in the nursing care process of patients with pyelonephritis, will improve their health satisfying their needs and achieving therapeutic success through comprehensive and effective care.
La pielonefritis es una infección del tracto urinario alto que se caracteriza por la invasión bacteriana de la pelvis y el parénquima renal de uno o ambos riñones y que puede causar complicaciones que comprometen la vida del paciente. En el año 2016 a nivel nacional se reportaron 1948 casos de pielonefritis de los cuales 311 afectaron a hombres y 1635 a mujeres debido a que son las más propensas a contraer esta enfermedad y otras relacionadas con las vías urinarias por su anatomía urogenital. La Escherichia coli, es la principal bacteria responsable de la mayoría de los casos de pielonefritis. El objetivo de este trabajo fue elaborar el proceso de atención de enfermería basado en el pensamiento crítico en la valoración, diagnóstico, planificación, ejecución y evaluación para la toma de decisiones en la atención del paciente y a su vez relacionarlo con la teoría de Marjory Gordon, que permite realizar una valoración de los patrones funcionales que constituyen un pilar fundamental en la identificación de los problemas reales o potenciales en los individuos. Se utilizó una metodología fundamentada en la investigación bibliográfica de fuentes como el internet, libros, artículos de revistas que fueron la base fundamental para la obtención de la información necesaria en la elaboración del presente trabajo investigativo. En conclusión, los planes de acción elaborados y aplicados en el proceso de atención de enfermería del paciente con pielonefritis, mejorará su estado de salud satisfaciendo sus necesidades y logrando el éxito terapéutico mediante un cuidado integral y eficaz.
Keywords: PROCESO DE ATENCION DE ENFERMERIA; PIELONEFRITIS; PENSAMIENTO CRITICO; PATRONES FUNCIONALES